THE EFFECTIVENESS OF WEB- BASED COMMUNICATION AMONG THE PARTIES INVOLVED IN SCHOOL, NATIONAL EDUCATION DIRECTORATE, AND INDUSTRY COOPERATION - THE VIEWS TOWARDS THE APPLICATION OF A DEVELOPED SOFTWARE - Ozmen, Fatma; Karabatak, Songul (Lookus Scientific, 2013)
In order to facilitate the communication between the parties involved in school-industry cooperation, this study was conducted to develop and implement a web-based software, and to determine the effectiveness of web-based communication between the parties in the context of the implemented software. Along with the goal of the study, at the end of the software application, to derive the opinions about the effectiveness of web-based communication relying on the applied software, Provincial Directorate of Education, three vocational schools, and three business corporations where the students were attending in order to complete their vocational skill training, were included in the study. As total the views of 16 people were gathered through interviews. As a result of the implementation of the developed software, it was detected that the communication among Provincial Directorate of Education, business corporations and schools by using information and communication technologies was cheaper, faster and more effective than by using other types of communication like paper-pencil communication or communication with the coordinator teacher once a week; and participants opinions were positive about the web based application. The prototype web based software developed for this study is considered effective for providing the quality of communication of vocational and technical education. The findings revealed also that lack of technological infrastructure and lack of adequate knowledge and experiences were substantial drawbacks for realizing web-based communication.
6th Knowledge Cities World Summit (KCWS) -- SEP 09-12, 2013 -- Istanbul, TURKEY
Keywords: Vocational training; web-based communication; effectiveness; schools; enterprises